In vitro aflatoxin adsorption capacity of some indigenous aflatoxin adsorbents - CHATURVEDI, V B; SINGH, K S; AGNIHOTRI, A K (The Indian Journal of Animal Sciences, 2014)
Shelkhari, Multani M and Bentonite were treated with spdium chloride and calcium chloride as well as combination of both solutions. Fine grinding of these adsorbents was done for increasing surface area. Aflatoxin adsorption on these adsorbents was tested using aflatoxin B1 solutipn in methanol and compared with a commercial adsorbent (CA). The adsorbents aflatoxin complex was subsequently washed with methanol to test the strength of aflatoxin adsorption. Aflatoxin adsorption on CA was 85.39% and only about 6.0% aflatoxin was eluted with methanol. Aflatoxin adsorption on Shelkhari was 32.53% only 4.39%. Aflatoxins remained adsorbed after washing with methanol. Adsorption of aflatoxin B, on untreated bentonite, hydrated calcium bentonite, hydrated sodium bentonite, hydrated sodium calcium bentonite was 67.39,55.51 ,80.83 and 68.55% respectively. Per cent adsorption of aflatoxin B1 on Multani (M), hydrated calcium Multani(M), hydrated sodium Multani (M) and hydrated sodium calcium Multani was 79.42,53.28,73.86 and 61.61 %, respectively. Among various materials CA and hydrated sodium bentonite had highest aflatoxin adsorption capacity.